Evaluation of Problem-based Learning Method for Teaching Islamic Education Courses to Students of Shiraz University of Medical Sciences - Shamsaei, Maryam (Dinamika Ilmu, 2020)
Emphasis on teaching religious education in the university and raising the level of religious awareness of students in parallel with specialized education, raises attention to the important point that the set of Islamic education courses was in line with the demands and desires of students? The aim of this study is to an increase of the analytic mood among the students and faculty members of the department of Islamic education by the teaching method of Problem-based learning. The present study was performed cross-sectionally on students of Shiraz University of Medical Sciences in Islamic education courses that they had taken as a general course. One of the strengths of this method is the student-centered and process-oriented instead of text-centric and moving from central memorization to research-oriented.